(untitled) (Palimpsesto, 2022)
The nascent work of the 1990s vindicates the populations displaced by the official discourses of a story told by the victors. The defeated appear as a question, wrapped in a silence that does not bother the official narratives. In the cases of the social revolutions in Mexico (1910), Bolivia (1952) and Cuba (1959) there are hidden roles within. The following essay intends to interfere in those protagonists, investigating the demands and actions that mobilized the native and afro-descendant population to participate. The guiding questions refers to: What were the demands and actions of the indigenous and afro-descendant populations in the revolutionary experiences? In the same way, it tries to give us an answer to: Why do we talk about the peasantry or workers, hiding the specificities of the original people? How did the revolutionary movements react to the demands? This essay aims to bring a look as a proposal to rediscover ourselves in the history of Latin America.